(untitled) - Chbosky, Stephen (New York, 2019)
"This haunting novel about the dilemma of passivity vs. passion marks the stunning debut of a provocative voice in contemporary fiction. This is the story of what it's like to grow up in high school. More intimate than a diary, Charlie's letters are singular, hilarious, and devastating." --
Charlie is a freshman. And while he's not the biggest geek in the school, he is by no means popular. He's a wallflower-- shy and introspective, and intelligent beyond his years, if not very savvy in the social arts. We learn about Charlie through the letters he writes: trying to make friends, family tensions, exploring sexuality, experimenting with drugs-- and dealing with his best friend's recent suicide. -- from first edition
Keywords: Mental illness; High school students; Dysfunctional families; Young adult fiction; Friendship; Epistolary fiction; Bildungsromans; Epistolary fiction; Bildungsromans; Fiction; Epistolary fiction; Bildungsromans